Elizabeth Scheu Close : a life in modern architecture - Hession, Jane King, 1951- (University of Minnesota Press, 2020)
"Elizabeth "Lisl" Scheu Close (1912-2011) was the first female modern architect in Minnesota. Over her 60-year career, she designed more than 150 residences in the state, which were stylistically rooted in Austrian and other European modern movements of the 1920s and 30s. The work of architect Adolf Loos was a primary influence -Close grew up in the 1912 Loos-designed Scheu House, a seminal early modern house in Vienna, Austria. In 1938 with her husband Winston Close, she cofounded the first practice in Minnesota dedicated to modern architecture. The book traces Lisl's life, education, and career from pre-World War I Vienna, to MIT, to Minnesota. Lisl was in the vanguard of professionally-trained women architects. Not only was she perceived as a "woman in a man's field" when she launched her career, she was also committed to a design aesthetic then not widely adopted by the public or the profession. Modernism, to Lisl, meant the design of buildings that "fit the modern style of living," or those that were practical, efficient, durable, and of their time"-- Provided by publisher.
Keywords: Close, Elizabeth Scheu, -- 1912-2011.; Architects -- Minnesota -- Biography.; Architects -- United States -- Biography.; Women architects -- Minnesota -- Biography.; Women architects -- United States -- Biography.; Femmes architectes -- États-Unis -- Biographies.; Femmes architectes -- Minnesota -- Biographies.; Architectes -- États-Unis -- Biographies.; Architectes -- Minnesota -- Biographies.; Modern (late 19th Century to 1945); History.; ARCHITECTURE.; Women.; BIOGRAPHY & AUTOBIOGRAPHY.; Women architects; Architects; United States; Minnesota; collective biographies.; Biographies; Biographies.